Relative availability of transferrin-bound iron and cell-derived iron to aerobactin-producing and enterochelin-producing strains of Escherichia coli and to other microorganisms. - Brock, J H (1991)
A method is described for determination of the relative availability of transferrin-bound iron and cell-derived iron to microbial iron-scavenging mechanisms. This involved incubation of parallel cultures of microorganisms in dialysis tubes placed in RPMI 1640 tissue culture medium containing 30%-iron-saturated transferrin and K562 erythroleukemia cells. In one culture the transferrin was labelled with 59Fe and in the other the cells were labelled, and the relative uptake of radioiron by the microorganisms determined. The results showed that Staphylococcus epidermidis and Staphylococcus aureus acquired iron predominantly from cells, while Candida albicans and the enteropathogenic Escherichia coli NCTC 8623 tended to acquire iron from transferrin. E. coli K-12 strains W3110 and LG1705, which (like NCTC 8623) produce the siderophore enterochelin but not aerobactin, acquired predominantly transferrin-bound iron, whereas the related E. coli strains LG1315 and LG1628, which produce aerobactin but not enterochelin, showed a preference for cell-derived iron. When the cells were incubated in the presence of 59Fe-labelled transferrin and 55Fe-labelled ferritin, no difference in relative availability of iron to E. coli was observed, suggesting that differences in the ability of aerobactin and enterochelin to remove iron from intracellular ferritin were not responsible for this preference. These results may help to explain why production of aerobactin, despite its relatively low affinity for iron, is more closely associated with invasiveness in E. coli than is enterochelin production. Reduced availability of cell-bound iron during inflammation may contribute to antimicrobial defenses.